Dampak Pandemi Covid-19 Terhadap Ekonomi Masyarakat di Nusa Tenggara Barat - Rosiady Husaenie Sayuti; Siti Aisyah Hidayati (Prodi Sosiologi Universitas Mataram, 2020)
The purpose of this research is to find out the economic impact of the Covid-19 Pandemic on the people of NTB. Community life has changed since the implementation of Large-Scale Social Restrictions (PSBB) by the Government. These changes are felt in various areas of the economy, namely income, employment, expenditure and the purchasing system carried out by the community. This research uses descriptive quantitative method. Descriptive research is research conducted with the aim of describing the conditions that took place when the research was conducted. Thus this research is able to clearly portray the economic impact experienced by the people of NTB due to the Covid-19 pandemic. Data collection is carried out using the Google Form tool which is distributed through various existing social media facilities, such as WhatsApp Groups, Facebook, and Twitter. The data scale used is the Likert Scale. Respondents in this study were individuals, namely the people of West Nusa Tenggara. The sample used in this study were 342 respondents. The results showed that most respondents felt the impact of the Covid 19 pandemic from an economic perspective. This is indicated by the answers of respondents who mostly stated that their income received had decreased but could still meet their daily needs, limited employment opportunities, increased expenditure and was dominated by the purchase of foodstuffs. Purchases made online are the choice of respondents. The conclusion of this study shows that this pandemic has a significant effect on people's lives, both those with civil servant and non-PNS backgrounds and those who live in rural and urban areas.